Simulation Analysis and Prediction of Wear for Neck Journal of Shifting Slider on AMT - Yuwei Liu; Ye Wang; Chongzhi Fu; Yuanzhi Sun; Hao Chen; Zixi Wang (Jixie chuandong)
In order to ensure the service life of slider and improve the shift quality，numerical simulation is carried out for the wear between the slider journal and the shift fork during gear shifting. A finite element model is established，and based on the heat transfer theory，the thermal boundary conditions of the shift fork and the slider are set，and the wear amount and temperature distribution cloud of the shift slider at the end of a single shift in the synchronization process is obtained. Based on the Archard wear theory，the wear amount at the end of a single shift is calculated. Through Box-Behnken design method，the finite element simulation is carried out through the required 17 experimental points，and the linear regression prediction model of the wear amount is obtained through response surface analysis，the influence of the shift force，rotation angle，and friction coefficient on the wear amount of the slider is analyzed. The research results show that the rotation angle has the most significant influence on the journal wear.